Degradação de glifosato (n-fosfonometil-glicina) por fungos isolados de solo da floresta amazônica - Corrêa , Lilian de Oliveira (2013)
The increase in cultivated areas promotes the successive increase in the use of pesticides, standing out pesticides, fungicides and herbicides, these cause environmental impact and harm to animals including to the man. Among the herbicides, Glyphosate is the most used in the world. Understanding that bioremediation is a control alternative for this herbicide, the present study aimed, evaluate the degradation of glyphosate using fungi isolates from a soil sample of Amazon rainforest. For this purpose: a) isolation and identification of fungi from a sample was carried out of Amazonian soil contaminated with glyphosate, b) the capacity of fungal isolates of use glyphosate as a source of phosphorus and carbon and c) used analytical methods (spectrometry, TLC and HPLC-MS) to analyze glyphosate degradation and metabolism by isolates. How results, it was observed that the fungi isolated from a soil sample of the Amazon Forest, belonged to the Phylum Ascomycota specifically to the genera Penicillium (60%), Aspergillus (26%) and Trichoderma (8%). The isolates that had the highest biomass and used glyphosate as possible phosphorus source, were the Aspergillus 2B112, Penicillium 4A21, Penicillium 4A211, Penicillium 6B221 and Penicillium 6B112. The isolate that possibly best used glyphosate as possible carbon source was Aspergillus 2B112. The colorimetric / spectrophotometric method demonstrated that the Penicillium 4A211, Aspergillus 2B112 and Penicillium 4A21 isolates degraded the glyphosate in 42.7%, 36.4% and 34.91%, respectively in 14 days. Thin layer chromatography (TLC) demonstrated the presence of glyphosate in the filtrates of the cultures and HPLC-MS demonstrated that Penicillium 4A 211 produces the metabolites AMPA and Sarcosine from glyphosate catabolism.